2015
DOI: 10.1186/s12967-015-0704-9
|View full text |Cite
|
Sign up to set email alerts
|

The Cooperative Health Research in South Tyrol (CHRIS) study: rationale, objectives, and preliminary results

Abstract: The Cooperative Health Research In South Tyrol (CHRIS) study is a population-based study with a longitudinal lookout to investigate the genetic and molecular basis of age-related common chronic conditions and their interaction with life style and environment in the general population. All adults of the middle and upper Vinschgau/Val Venosta are invited, while 10,000 participants are anticipated by mid-2017. Family participation is encouraged for complete pedigree reconstruction and disease inheritance mapping.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
115
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 78 publications
(122 citation statements)
references
References 75 publications
1
115
0
Order By: Relevance
“…This strategy was used in the Cooperative Health Research In South Tyrol (CHRIS) study [40], a population-based study aiming to investigate the genetic and molecular basis of age-related common chronic conditions and their interaction with life-style and environment in the general population [28]. To recruit participants from rural areas to the study, village information meetings, broadcasts of information to the public through the local media and web-based recruitment were combined to maximise family participation.…”
Section: Resultsmentioning
confidence: 99%
“…This strategy was used in the Cooperative Health Research In South Tyrol (CHRIS) study [40], a population-based study aiming to investigate the genetic and molecular basis of age-related common chronic conditions and their interaction with life-style and environment in the general population [28]. To recruit participants from rural areas to the study, village information meetings, broadcasts of information to the public through the local media and web-based recruitment were combined to maximise family participation.…”
Section: Resultsmentioning
confidence: 99%
“…The present study examined 4,979 participants of the population-based CHRIS study of primarily native German speakers (95%), set in an Alpine region of northern Italy. 31 The CHRIS study has been investigating the epidemiology of cardiovascular and neurological conditions typical of human ageing. All participants underwent a session at the study center that includes physical examinations, a structured clinical interview, and self-administered questionnaires.…”
Section: Study Populationmentioning
confidence: 99%
“…Participants had an age range of 18 to 93 years and gender-age distribution similar to that of the adult population living in the region, with slight underrepresentation of the elderly (aged 75 years). 31 The study was approved by the local Research Ethics Committee. All participants gave written informed consent.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that HILIC-MS methods are suitable for separating polar metabolites [31,19]. Since we are interested in polar metabolites, in this study, we analyzed the metabolomes extracted from VAMS by using a HILIC-MS method designed for the large-scale studies of plasma and serum samples [34]. All extracting solutions, except for pH 9 solution, gave clear (uncolored) extracts.…”
Section: Europe Pmc Funders Author Manuscriptsmentioning
confidence: 99%